Dificuldades no desempenho ocupacional de gestantes - Amorim, Daniele (Universidade Federal de São Carlos, 2022)
The literature points out that pregnancy is a phenomenon that presents changes and unique perceptions, sensations and perceptions. In general, all physical, social, emotional, economic, familiar and occupational changes occur in a healthy and uncomplicated way. Thus, these changes can affect the occupational performance of women, in relation to Activities of Daily Living (ADLs) and in Instrumental Activities of Daily Living (IADLs). This study was developed through a descriptive qualitative research. Data collection started with an application of a semi-structured interview, composed of nine open questions and, later, the application of the Canadian Occupational Performance Measure (COPM). Data were transcribed and analyzed using the Content Analysis technique, in thematic mode. The results of the study show that the difficulties in the occupational performance of pregnant women are related, above all, to self-care activities, functional mobility and home tasks. Regarding the COPM, the activities with the greatest predominance in the responses of the pregnant women were related to self-care, followed by productive activities. It is hoped that with the results obtained, the study will help to understand the possible difficulties in the occupational performance of basic and instrumental activities of pregnant women.
Difficulties in the occupational performance of pregnant women
Keywords: Gestação; Desempenho ocupacional; Atividades de vida diária; Atividades instrumentais de vida diária; Pregnancy; Occupational performance; Activities of daily living; Instrumental activities of daily living; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL